Morning vs. evening maximal cycle power and technical swimming ability - Deschodt, V. J.; Arsac, L. M. (The Journal of Strength and Conditioning Research, 2004)
The aim of this study was to observe diurnal influences on maximal power and technical swimming ability at three different times (8 AM, 1 PM, and 6 PM). Prior to each test, tympanic temperature was taken. Maximal power was analyzed by cycle tests. Stroke length, stroke rate, hand pattern, and swimming velocity were recorded between the 20th and the 28th m of the 50-m freestyle. Temperature varied ±0.4° C between morning and evening. Concomitantly, maximal power (+7%) and technical ability (+3% in stroke length, +5% in stroke rate and changes in underwater hand coordinates) were greater in the evening. The present study confirms and specifies diurnal influences on all-out performances with regard to both maximal power and technical ability. Thus, when swimmers are called upon to perform at a high level in the morning, they should warm up extensively in order to "swamp" the diurnal effects of the morning.